Accessibility of disabled facilities at Fi-Sabilillah Mosque, Cyberjaya/ Nor Izana Mohd Shobri, Intan Bayani Zakaria and Norazlin Mat Salleh - Mohd Shobri, Nor Izana; Zakaria, Intan Bayani; Mat Salleh, Norazlin (Universiti Teknologi MARA, Perak, 2018)
All mosques need to be equipped with facilities for people with disabilities (PWD) in fulfilling with the requirements of the Malaysian Standard Code of Practice (MS) on Access of Disabled Persons. However, most mosques in Malaysia do not fulfil these requirements in terms of providing facilities for the PWDs. This adversely affects the PWDs to engage in the social and economic mainstream. The research aim is to classify the conformity of disabled facilities provided at Fi-Sabilillah Mosque, Cyberjaya in Selangor. The two research objectives were established (1) to identify the spectrum of disabled facilities provided at the Fi-Sabilillah Mosque, Cyberjaya in Selangor and (2) to determine the compliance of the disabled facilities as outlined in the MS. Purely qualitative methods were adopted in terms of visual study, audit survey and a semi-structured interview with the architect. A condition audit checklist was established using document analysis method on three main documents. The findings indicate 58% of the facilities are available and follow the MS, 13 % items were available but not comply with the standard measurement and 29% of the disabled facilities are not available within the mosque. Therefore, it can be stated that there is poor design, weak enforcement and lack of awareness among the stakeholder, local authority and the designer of the mosque regarding the disabled facilities. Therefore, enforcement is a priority to ensure the needs and right of the disabled user are considered in designing a mosque.